Moral Dilemmas in Contact-Based Care: The Relevance of Moral Case Deliberation for Forensic Psychiatry - Gerritsen, Sylvia; Widdershoven, Guy A. M.; Bossenbroek, Bernard J.; Voskes, Yolande (Frontiers in Psychiatry, 2020)
Currently, forensic psychiatry shows a shift from a control-based to a contact-based approach. Working from contact may, however, entail new moral questions and dilemmas. How to secure safety when focusing on contact? Does contact imply being physically close to the patient or should one refrain from intimate relations? In order to help care professionals to deal with these moral issues, clinical ethics support can be useful. A specific approach in clinical ethics support is Moral Case Deliberation (MCD). An MCD is a structured dialogue between professionals on a moral issue they experience in practice, following a conversation method and guided by a facilitator. In this paper, we describe the background and procedures of MCD. Furthermore, we present a case example in which care professionals reflect on the moral question of whether provision of care in forensic psychiatry may entail physical closeness. The MCD shows that an open conversation results in a better understanding of different perspectives, and creates the basis for finding a joint way to proceed in the case. We conclude that MCD can enable professionals to reflect on moral issues and develop shared values in forensic psychiatry.